Prefrontal-Amygdala Connectivity and State Anxiety during Fear Extinction Recall in Adolescents - Ganella, Despina E.; Barendse, Marjolein E. A.; Kim, Jee H.; Whittle, Sarah (Frontiers in Human Neuroscience, 2017)
While deficits in fear extinction recall have been suggested to underlie vulnerability to anxiety disorders in adolescents, the neurobiology of these deficits remain underexplored. Here we investigate the functional connectivity of the ventromedial prefrontal cortex (vmPFC) and dorsolateral PFC (dlPFC) underlying extinction recall in healthy adolescents, and assess associations between FC and state/trait anxiety. Adolescents (17) and adults (14, for comparison) completed a fear-learning paradigm involving extinction and extinction recall during a functional magnetic resonance imaging session, in which skin conductance response (SCR) was recorded. Psychophysiological interaction analyses revealed that during extinction recall there was significant negative connectivity between the vmPFC and amygdala in adults, but not adolescents. vmPFC-amygdala connectivity was positively correlated with SCR. Adolescents showed significant negative functional connectivity between the dlPFC and the left and right hippocampus, and the amygdala, which was positively correlated with state anxiety. Recall was also associated with negative connectivity between the dlPFC and thalamus, posterior cingulate cortex, fusiform gyrus and pallidum in adolescents. These results demonstrate that fear extinction recall in healthy adolescents is associated with functional connectivity between prefrontal and limbic brain regions, and suggest that alterations in connectivity may be associated with vulnerability to anxiety in adolescence.